1996
DOI: 10.1007/bf01880741
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory follow-up of aortic dissection: comparison between computed tomography and biplane transesophageal echocardiography

Abstract: Both CT and TEE are atraumatic, safe and accurate techniques for serial follow-up imaging of patients treated for aortic dissection. Information provided by CT is largely redundant, rather than additive, to that provided by TEE. The latter should be probably preferred for shorter imaging time, accuracy and convenience, although CT might still play a role in selected cases of ambiguous TEE results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Other authors have found effusion to be less common. Maffei et al 12 reported finding pleural effusion by CT in only 4 of 44 patients with treated AAD; the acute period of aortic dissection was not studied. Our patients were followed up for Ͼ 1 month after onset of AAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have found effusion to be less common. Maffei et al 12 reported finding pleural effusion by CT in only 4 of 44 patients with treated AAD; the acute period of aortic dissection was not studied. Our patients were followed up for Ͼ 1 month after onset of AAD.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] However, few reports have considered the frequency and pathogenesis of pleural effusion occurring during the clinical course of AAD. [12][13][14] The aim of this study was to clarify the clinical significance of pleural effusion in patients with AAD, and to investigate the relationship of these effusions to associated clinical events including inflammatory reactions. We evaluated CT and other findings in patients with presumptive diagnoses of AAD.…”
mentioning
confidence: 99%
“…Less than 10% of operated patients with type I dissection show an obliteration of the false lumen [6,[250][251][252][253][254][255] .…”
Section: Natural History Of Aortic Dissection and Prognosismentioning
confidence: 99%
“…Die transösophageale zweidimensionale und Dopplerechokardiographie (10,11,13,14,16,17) hat sich neben den modernen bildgebenden Verfahren wie der Spiral-Computer- (18,19,20,21,22) in der Akut-und Verlaufsdiagnostik von Aortendissektionen wegen der hochauflösenden Morphologie und Flußdarstellung bewährt. Ziel der Verlaufsdiagnostik bei Patienten mit chronischen Aortendissektionen ist die Beurteilung der Aortenweite, das Erkennen von Aneurysmabildungen des falschen Lumens sowie die frühzeitige Diagnose von Komplikationen, wie Redissektionen, drohenden Rupturen und Aortenklappeninsuffizienzen (10,11,16,17).…”
Section: Diskussionunclassified
“…Ziel der Verlaufsdiagnostik bei Patienten mit chronischen Aortendissektionen ist die Beurteilung der Aortenweite, das Erkennen von Aneurysmabildungen des falschen Lumens sowie die frühzeitige Diagnose von Komplikationen, wie Redissektionen, drohenden Rupturen und Aortenklappeninsuffizienzen (10,11,16,17). Regelmäßige klinische Verlaufsuntersuchungen in Kombination mit bildgebenden Verfahren sind vor dem Hintergrund von Reoperationsraten zwischen 13 und 30 % in 10 Jahren absolut indiziert (6,7,8).…”
Section: Diskussionunclassified